Betulinic Acid Acts in Synergism with Imatinib Mesylate, Triggering Apoptosis in MDR Leukemia Cells - Stutz, Claudia; Fontão, Ana Paula Gregório Alves; Silva, Gustavo Werneck de Souza e; Seito, Leonardo Noboru; Perdomo, Renata Trentin; Sampaio, André Luiz Franco (Planta Medica, 2024)
Chronic myeloid leukemia (CML) is a myeloproliferative disease, characterized by the presence of the oncogene BCR-ABL. Imatinib mesylate (IMA) is the first-line treatment for CML, and some treatment resistance has been reported. Natural products are rich sources of bioactive compounds with biological effects, opening a possibility to alter cell susceptibility to drugs such as imatinib. Herein, we evaluated the interference of betulinic acid and ursolic acid in glycoprotein P (P-gp) activity and the possible synergistic effect when associated with IMA by the Chou-Talalay method. Ursolic acid presented an IC50 of 14.0 µM and 19.6 µM for K562 and Lucena 1, respectively, whilst betulinic acid presented an IC50 of 8.6 µM and 12.5 µM for these cell lines. Evaluation of the combination of terpenoids and imatinib mesylate revealed that ursolic acid or betulinic acid acts in synergism with IMA, as indicated by the combination indexes (CI<1). Analysis of annexin V labeling demonstrated that a combination of IMA with betulinic acid enhances the inhibition on cell proliferation via the apoptosis pathway, with caspases 3/7 activation after 24 hours of treatment and inhibition of the STAT5/survivin pathway, decreasing cell viability. The combination of natural products and IMA on a multidrug-resistant leukemia cell line is a promising strategy for CML treatment.
Keywords: cancer; betulinic acid; ursolic acid; synergism; MDR